Multimodal training with dual-task enhances immediate and retained effects on dual-task effects of gait speed not by cognitive-motor trade-offs in stroke survivors: a randomized controlled trial. - Chuang, Li-Ling; Hsu, An-Lun; Lin, Yun-Hsuan; Yu, Meng-Hua; Hu, Gwo-Chi; Ou, Yu-Chih; Wong, Alice May-Kuen (Disability & Rehabilitation, 2025)
Purpose: Individuals who have experienced stroke may benefit from dual-task related training to improve gait speed performance. Whether noted improvements reflect true effects on gait or cognitive-motor trade-offs still remains unclear. Therefore, this study aimed to investigate the effects of dual-task training on dual-task effects of both walking and cognitive domains in stroke survivors. Materials and methods: Forty-four individuals with stroke were randomized to dual-task or single-task training groups. Both groups exercised three 60-minute sessions per week for 4 weeks. The primary outcomes were dual-task effects on gait speed and cognitive score. Outcomes were assessed before and after the intervention and 1-month follow-up. Results: While both groups exhibited improvement in absolute gait speed under dual-task conditions, the dual-task training group demonstrated superior results by providing an additional gain on dual-task effects of gait speed. Compared to single-task training, dual-task training exhibited a significant improvement in dual-task effects of gait speed at post-treatment and follow-up. Regarding the dual-task effects on cognitive scores, no significant differences within and between groups after training were observed. Conclusion: Dual-task training enhances immediate and retained effects on the dual-task effects of gait speed in individuals with stroke, not by cognitive-motor trade-offs. Trial registration: URL: . ClinicalTrials.gov Identifier: NCT02686515 IMPLICATIONS FOR REHABILITATION: Dual-task interference during walking has important consequences for stroke survivors to walk safely. Multimodal training with dual-task enhances immediate and retained effects on the dual-task effects of gait speed in individuals with stroke, not by cognitive-motor trade-offs. Clinicians are encouraged to incorporate multimodal training with dual-task into the exercise routines to enhance walking under dual-task conditions in stroke survivors.